2017
DOI: 10.1186/s13195-017-0250-1
|View full text |Cite
|
Sign up to set email alerts
|

DHA brain uptake and APOE4 status: a PET study with [1-11C]-DHA

Abstract: BackgroundThe apolipoprotein E ɛ4 (APOE4) allele is the strongest genetic risk factor identified for developing Alzheimer’s disease (AD). Among brain lipids, alteration in the ω-3 polyunsaturated fatty acid docosahexaenoic acid (DHA) homeostasis is implicated in AD pathogenesis. APOE4 may influence both brain DHA metabolism and cognitive outcomes.MethodsUsing positron emission tomography, regional incorporation coefficients (k*), rates of DHA incorporation from plasma into the brain using [1-11C]-DHA (J in), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 42 publications
3
49
0
Order By: Relevance
“…Also in 2017, the same group [13] reviewed original articles, systematic reviews, and meta-analyses of omega-3 studies in AD that were published before August 20, 2016 and concluded that while randomized clinical trials of omega-3 in symptomatic AD reported negative findings, several observational and clinical trials of omega-3 in the pre-dementia stage of AD suggest that omega-3 supplementation might slow early memory decline in 4 carriers. Tambini et al [97] conducted an in vitro experiment whose results are consistent with the increased lipid metabolism observed by Yassine et al [96]. Using an astrocyte-conditioned media model, this group measured the synthesis of phospholipids and cholesteryl esters and reported a significant increase in cells treated with APOE 4containing astrocyte-conditioned media as compared to those treated with APOE 3-containing-astrocyteconditioned media.…”
Section: Biochemical Differences Possibly Related To Neural Stress Insupporting
confidence: 57%
See 2 more Smart Citations
“…Also in 2017, the same group [13] reviewed original articles, systematic reviews, and meta-analyses of omega-3 studies in AD that were published before August 20, 2016 and concluded that while randomized clinical trials of omega-3 in symptomatic AD reported negative findings, several observational and clinical trials of omega-3 in the pre-dementia stage of AD suggest that omega-3 supplementation might slow early memory decline in 4 carriers. Tambini et al [97] conducted an in vitro experiment whose results are consistent with the increased lipid metabolism observed by Yassine et al [96]. Using an astrocyte-conditioned media model, this group measured the synthesis of phospholipids and cholesteryl esters and reported a significant increase in cells treated with APOE 4containing astrocyte-conditioned media as compared to those treated with APOE 3-containing-astrocyteconditioned media.…”
Section: Biochemical Differences Possibly Related To Neural Stress Insupporting
confidence: 57%
“…Young subjects having at least one copy of the 4 allele reportedly possess a number of advantages that might facilitate survival in harsh environments including the following among others: more rapid improvement in VO 2max following exercise [51]; increased fertility at high pathogen burdens [52,53]; more rapid infant development [105]; prophylaxis against cognitive deficits associated with severe diarrhea [122][123][124]; resistance to certain infections, e.g., hepatitis [76] and malaria [83]; faster reaction times [121]; better spatial memory [111,102,119,120]; and slight superiority in direct or indirect measures of IQ [135,134,126,141]. Some of these advantages appear to come at the expense of differences in neural processing that might place higher metabolic demands per unit time on the brains of young 4 carriers [143,111,96].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased rate of DHA incorporation into neuronal membranes reported by Yassine et al [39], and higher brain activity seen in young, healthy APOE ε4-positive individuals both support a higher rate of turnover in synaptic macromolecules associated with the APOE ε4 allele, regardless of explanation. Although neurogenesis can occur in the adult hippocampus [52], and increased neurogenesis increases the rate of synapse formation, synaptogenesis and synaptic pruning occur in the absence of neurogenesis.…”
Section: Synaptic Toxicity Increases With Macromolecular Turnover Ratementioning
confidence: 84%
“…Recently, Yassine, et al [39] used positron emission tomography to demonstrate increased docosahexaenoic acid (DHA) uptake in several brain regions in APOE ε4 carriers. In the AD-susceptible entorhinal sub-region, the mean global gray matter DHA incorporation coefficient was 16% higher among APOE ε4 carriers (n = 9) than among APOE ε3 and APOE ε2 carriers (n = 13, p = 0.046).…”
Section: Importance Of the Apoε Genotypementioning
confidence: 99%